Islamic Behavior Habits As a Cultural School (Case Study in SMAN 3 Bojonegoro) - Muh Muhtarom (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
Abstract: This Reseach aimed to explore how Islamic behavior habits strategy in SMAN 3 Bojonegoro, how Implementation of Islamic behavior habits in SMAN 3 Bojonegoro, and how the implications of Islamic behavior in SMAN 3 Bojonegoro. The method of this research was qualitative approach with case study design, its location is in State Senior High School 3 Bojonegoro, source of informant, event, location and document, primary and secondary data, data collecting technique with participant observation, interview and documentation. Data analysis with single case analysis, while checking its data validity by using peer discussion, triangulation method, triangulation of data source, time triangulation. The results of this study showed that: 1) Planning habituation of Islamic behavior starting from the formulation of vision and mission of Islami, until the preparation of standard ubudiyah. To familiarize Islamic behavior, Islamic religious education teachers familiarize religious behavior and plan religious activities in educational institutions. Planning of such religious activities as one of the means to create a religious atmosphere as the development of Islamic education learning in the school, 2) Habituation of Islamic behavior starting from daily activities, weekly, monthly to annual, and 3) Islamic behavior habits can form the Muslim personality on students in educational institutions. The Muslim person with the qur'ani character could be formed through the habituation of religious activities in the institution. Keywords: Habituation, Islamic Behavior.